Hepatic steatosis: a role for citrulline. Issue 5 (September 2016) - Jegatheesan, Prasanthi; De Bandt, Jean-Pascal
Abstract : Purpose of review: The high worldwide prevalence of nonalcoholic fatty liver disease (NAFLD) makes it a major public health issue. Amino acids offer a promising approach for its prevention, and several experimental studies highlight the nutritional importance of citrulline in this setting. The purpose of this review is to discuss the potential interest of citrulline in the prevention and treatment of NAFLD. Recent findings: Current findings shed light on the role of the gut–liver, adipose tissue–liver, and muscle–liver axes in NAFLD progression. Recent experimental studies have produced evidence for a role of citrulline in controlling the pathophysiological mechanisms involved in NAFLD through its action on these three axes. Data are needed to distinguish between direct and indirect effects of citrulline on the liver and between a specific effect and a nitrogen supply-related effect. Summary: Good level of experimental evidence suggests that citrulline supply may be associated with an attenuation of NAFLD development, but further human studies are now needed to support these findings. This review may help define novel strategies to control fatty liver diseases.